Peptidomic analysis reveals proteolytic activity of kefir microorganisms on bovine milk proteins. (15th April 2016) - Dallas, David C.; Citerne, Florine; Tian, Tian; Silva, Vitor L.M.; Kalanetra, Karen M.; Frese, Steven A.; Robinson, Randall C.; Mills, David A.; Barile, Daniela
Highlights: Kefir-induced degradation of milk proteins was examined via peptidomics. Kefir microorganisms released 609 peptides from milk proteins. Native milk enzymes degraded proteins to a lesser extent than kefir microorganisms. Kefir contains functional peptides that may affect consumer health. Abstract: Scope: The microorganisms that make up kefir grains are well known for lactose fermentation, but the extent to which they hydrolyze and consume milk proteins remains poorly understood. Peptidomics technologies were used to examine the proteolytic activity of kefir grains on bovine milk proteins. Methods and results: Gel electrophoresis revealed substantial digestion of milk proteins by kefir grains, with mass spectrometric analysis showing the release of 609 protein fragments and alteration of the abundance of >1500 peptides that derived from 27 milk proteins. Kefir contained 25 peptides identified from the literature as having biological activity, including those with antihypertensive, antimicrobial, immunomodulatory, opioid and anti-oxidative functions. 16S rRNA and shotgun metagenomic sequencing identified the principle taxa in the culture as Lactobacillus species. Conclusion: The model kefir sample contained thousands of protein fragments released in part by kefir microorganisms and in part by native milk proteases.